DYNAMIC TEAMWORK WITHIN A LEAN ORGANIZATION - Sasmita Mohanty , Bibhuti B Pradhan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Many manufacturing companies operate in a competitive and in part unpredictable market. This is illustrated by shorter product life cycles, decreased forecast accuracy within the supply chain and often new releases of products. In addition, the total amount of output and the work description are strongly fluctuating. Rigid organizations face significant challenges if they are unable to manage targets correctly and rapidly with all value stream processes. Such situations lead manufacturing firms to pass Lean Production Systems concepts on to other business divisions, such as growth and operation. The aim is therefore the creation of a Lean Enterprise which allows for the overall consideration of all processes across the whole value stream. Through this detailed process orientation all participants in the entire value chain can be connected together. Therefore it is important to consider both internal and external stakeholders. This can be regarded as one basic consideration for optimal coordination. Approaches that allow all processes within a Lean Organization to be dynamically organized have not yet been developed. Considering this subject, this paper extracts and describes an approach to the processes of all units across the entire value stream to decide objectives of the corporate enterprise strategy. Additionally processes can be modified rapidly to cope with competitive and volatile markets. Thereby a complex integration of all operations can be realized within a Lean Enterprise.